Application of Deep Learning for Reservoir Porosity Prediction and Self Organizing Map for Lithofacies Prediction - Hussain, Mazahir; Liu, Shuang; Hussain, Wakeel; Liu, Quanwei; Hussain, Hadi; Ashraf, Umar (Journal of applied geophysics, 2024)
While there is a connection between petrophysical logs and reservoir porosity, finding analytical solutions for this relationship is still difficult. This paper presents a novel approach for forecasting porosity and lithofacies by using a convolutional neural network (CNN) model in conjunction with a bi-directional long short-term memory (BLSTM) network. The BLSTM network uses a self-organizing map (SOM) technique to form connections between input and destination data. The SOM is used to organize depth intervals with similar facies into four separate clusters, each exhibiting internal consistency in petrophysical parameters. The CNN is responsible for extracting spatial characteristics, while the BLSTM network gathers comprehensive spatiotemporal components, guaranteeing that the model accurately represents the spatiotemporal aspects of log data. The accuracy of the model was verified by analyzing simulation logging data. The findings indicate that the BLSTM network model successfully recovers significant characteristics from logging data, resulting in improved estimate accuracy. In addition, Facies-01 has lower gamma ray levels in comparison to other facies. Facies-01 is also suggestive of pristine sandstone formations, which are greatly sought as reservoir rocks. The BLSTM network model is effective in predicting physical characteristics of reservoirs, offering a new method for precise reservoir characterization parameter prediction. •BLSTM model is constructed for the purpose of predicting reservoir porosity.•We proposed a new method for predicting porosity and lithofacies based on the CNN model.•SOM was used to arrange depth intervals with comparable facies.•Facies-01 has lower gamma ray levels in comparison to other facies.•The SOM model was validated through simulation logging data.